One dog and his boy - Ibbotson, Eva (Scholastic Press, 2012)
When lonely, ten-year-old Hal learns that his wealthy but neglectful parents only rented Fleck, the dog he always wanted, he and new friend Pippa take Fleck and four other dogs from the rental agency on a trek from London to Scotland, where Hal's grandparents live.